2014
DOI: 10.1021/jf502447e
|View full text |Cite
|
Sign up to set email alerts
|

Penta-O-galloyl-β-d-glucose Suppresses EGF-Induced eIF3i Expression through Inhibition of the PI3K/AKT/mTOR Pathway in Prostate Cancer Cells

Abstract: Approximately 70% of prostate cancer patients will develop bone metastasis in axial and other regions of the skeleton. Epidermal growth factor (EGF) generated from bone tissue contributes to prostate cancer metastasis. In a previous study, penta-O-galloyl-β-D-glucose (PGG) suppressed androgen-independent prostate cancer bone metastasis by transcriptionally repressing EGF-induced MMP-9 expression. This study utilized proteomics to analyze the effects of PGG in EGF-induced prostate cancer bone metastasis. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 30 publications
(56 reference statements)
1
11
0
Order By: Relevance
“…is result indicated that the MCF-7 breast cancer cell line treated with 60 μg/mL MPSE had elevated levels of ROS generation at 24 h treatment, in part due to the increase in the release of ROS from the damaged cells, a process so-called ROS-induced ROS release (RIRR) [42]. However, a further in-depth study focusing on the mitochondrial ROS generation, 16 Evidence-Based Complementary and Alternative Medicine determined by mitoSOX correlation with the effect of MPSE-treated breast cancer cells, must be performed to confirm this. Moreover, ROS produced in the mitochondria has been linked to mitochondrial membrane rupture and the loss of mitochondrial membrane potential (ΔΨm).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…is result indicated that the MCF-7 breast cancer cell line treated with 60 μg/mL MPSE had elevated levels of ROS generation at 24 h treatment, in part due to the increase in the release of ROS from the damaged cells, a process so-called ROS-induced ROS release (RIRR) [42]. However, a further in-depth study focusing on the mitochondrial ROS generation, 16 Evidence-Based Complementary and Alternative Medicine determined by mitoSOX correlation with the effect of MPSE-treated breast cancer cells, must be performed to confirm this. Moreover, ROS produced in the mitochondria has been linked to mitochondrial membrane rupture and the loss of mitochondrial membrane potential (ΔΨm).…”
Section: Discussionmentioning
confidence: 99%
“…PGG has attracted attention because of its therapeutic potential and has shown certain functional properties such as antimicrobial, anti-inflammatory, anticancer, antidiabetic, and antioxidant activities [15]. PGG possesses antiproliferative effects on a variety of cancer cells including prostate cancer [16], liver cancer [17], and breast cancer [18].…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorylation of PI3K activates the phosphorylation of Akt and mTOR, which have central roles in the regulation of cell proliferation, growth, and survival [35]. Many previous studies have shown that natural substances have the ability to suppress the PI3K/Akt/mTOR signaling pathway in several cancer cells, thus, targeting the PI3K/Akt/mTOR signaling pathway is a key strategy for the suppression of cancer [36][37][38]. The levels of phospho-PI3K, phospho-Akt, and phospho-mTOR decreased in RC-58T cells following exposure to sanggenol L treatment ( Figure 6A).…”
Section: Discussionmentioning
confidence: 99%
“…Poly-galloyl-glucopyranose or 1,2,3,4,6-penta-O-galloyl-βd-glucose (PGG), is a polyphenolic gallotannin synthesized by plants. Initially extracted from Rhus typhina (sumac) in 1990 by Hofmann and Gross, studies indicate that PGG has antidiabetic, antioxidant, anti-cancer and anti-inflammatory activities [26].…”
Section: Poly-galloyl-glucopyranosementioning
confidence: 99%
“…1, 2, 3, 4, and then incubated for 48 h. The induction pattern followed similar methods for this cancer cell line, as described in previous studies. We selected the PGG concentrations based on published literature describing PGG effects in several cell lines [26][27][28]31].…”
Section: Cell Culturementioning
confidence: 99%